Eradication in Patients Undergoing Gastrectomy: Diagnosis and Therapy - Youn I Choi; Jun-Won Chung (The Korean Journal of Helicobacter and Upper Gastrointestinal Research)
The role of Helicobacter pylori (H. pylori) eradication in patients undergoing gastrectomy for gastric cancer is unclear. Although European and Asian guidelines strongly recommend H. pylori eradication in patients who undergo endoscopic resection for early gastric cancer, these guidelines do not specify the tests useful for diagnosing H. pylori infection, the optimal timing and appropriate eradication regimens, and follow-up strategies in patients undergoing gastrectomy for gastric cancer. This review aims to update the guidelines for the diagnosis and management of H. pylori infection in patients undergoing gastrectomy for gastric cancer. We have focused on the following issues: 1) diagnostic tests for H. pylori infection in the remnant stomach, 2) optimal timing and regimen for H. pylori eradication, and 3) role of H. pylori eradication in reducing the risk of metachronous gastric cancer in the remnant stomach.